TECHNOLOGICAL DEVELOPMENT OF THE INDUSTRIAL-PHARMACEUTICAL SECTOR ASSOCIATED TO MATERIAL TRANSFORMATION PROCESSES - VALLEJO D., Bibiana M.; TORRES P., Norma S. (Vitae, 2009)
The present article gathers the most relevant results that were found while studying material transformation processes in the pharmaceutical industrial sector in the city of Bogota thus allowing the presentation of a panoramic vision of the state of technological development of this industry. The study was carried out in 157 companies that manufacture pharmaceutical products in the city. These companies transform materials for the sub sectors of medicine, phytotherapeutics, cosmetics and cleaning products. Using the size of the organizations in function of the number of employees as classification criteria, it was possible to correlate this aspect with descriptors selected by the investigating group to define indicators of technological development in the sector. These indicators were: product’s market, production lines, type of plant, plant’s utilization of its capacity, certifications, identification of the main problem in the Material Transformation Processes, automation of the line and role of the pharmaceutics.